Variation of 14C in Japanese Tree Rings Related to the Fukushima Nuclear Accident. Issue 4 (21st May 2019) - Varga, Tamás; Palcsu, László; Ohta, Tomoko; Mahara, Yasunori; Jull, A J Timothy; Molnár, Mihály
ABSTRACT: Radiocarbon ( 14 C) analysis was performed on Japanese cedar (Cryptomeria japonica) tree rings from Koriyama, Fukushima prefecture. Our primary aim was to detect any 14 C release from the Fukushima Dai-ichi nuclear power plant accident on 11 March 2011. We also completed and assessed the 14 C level in Japanese tree rings for the period of 1990–2014 because of the lack of environmental 14 C results in the Japanese island that time. For this reason, we used a trajectory model to investigate the air mass forward and backward trajectories at the area of the power plant and sampling site. The modeling data show that the air masses mainly moved to the Pacific Ocean, both during March 2011 and during the growing season (March–September). During the period 1990–2014 there was no significant 14 C excess in any of the samples, but there was a detectable Suess effect in almost every tree ring sample. The average fossil contribution was 0.83 ± 0.01% and the calculated anthropogenic component ratio, the 14 C excess varied between +0.5 and –1.6%. The Δ 14 C value decreased from 150.0‰ to 9.5‰ from 1990–2014, which follows the decline of the 14 C bomb peak, in addition to any detectable Suess effect.